Răspuns :
raspunsul este multt mai detaliat dar rezultatul final este -21
[tex]1 + 2 + ( - 3) + ( - 4) + 5 + ( - 6) + 7 + ( - 8) + 9 + ( - 10) + 11 + ( - 12) =[/tex]
[tex]1 + 2 - 3 - 4 + 5 - 6 + 7 - 8 + 9 - 10 + 11 - 12 = [/tex]
[tex]3 - 3 - 4 + 5 - 6 + 7 - 8 + 9 - 10 + 11 - 12 = [/tex]
[tex]- 4 + 5 - 6 + 7 - 8 + 9 - 10 + 11 - 12 = [/tex]
[tex]1 - 6 + 7 - 8 + 9 - 10 + 11 - 12 = [/tex]
[tex] - 5 + 7 - 8 + 9 - 10 + 11 - 12 = [/tex]
[tex]2 - 8 + 9 - 10 + 11 - 12 = [/tex]
[tex] - 6 + 9 - 10 + 11 - 12 = [/tex]
[tex]3 - 10 + 11 - 12 = [/tex]
[tex] - 7 + 11 - 12 = [/tex]
[tex]4 - 12 = - 8[/tex]